Antimicrobial efficacy of Nocardiopsis sp. MK_MSt033 against selected multidrug resistant clinical microbial pathogens - Muthukrishnan P.; Chithra Devi D.; Ashraf A. Mostafa; Khawla Ibrahim Alsamhary; Neveen Abdel-Raouf; Essam Nageh Sholkamy (Elsevier, 2020)
Background: Actinomycetes show an active role in microbial disease control and antimicrobial metabolism production and were shown the greatest potentialities as sources of antimicrobial agents. The past few decades, an extensive literature has accumulated on the production of bioactive compounds from actinomycetes, particularily genus Streptomyces. Methods: The actinomycetes were isolated with starch casein nitrate (SCN) agar medium. The prospective isolate was subjected to antimicrobial metabolites production. Further, the bio-extract was evaluated their biological properites by agar well diffusion assay and finally the extract was anaylized through GC-MS. Results: In the present study, isolated 9 actinomycetes and the isolates were examined for their antifungal activities. Of these nine isolates, the isolate MK_MSt033 picked out from the rest, hences, it showed significant control towards the selected microbial pathogens. The prospective strain MK_MSt033 was determined as Nocardiopsis sp. The strain displayed effective antimicrobial activities against both bacterial and fungal pathgoens such as Escherichia coli, Staphylococcus aureus, Pencillium sp., and Aspergillus flavus respectively. Subsequently the chemical nature of the compounds produced by the potential isolate MK_MSt033 and it was successfully determined by GC-MS and it were 18 compounds with different retention time. Conclusion: The identified isolate Nocardiopsis sp. MK_MSt033 exhibited potential antimicrobial activities against selected microbial pathogens. Thus, the soil inhabiting Nocardiopsis sp. has explored for pharmaceutically active compounds with promising medical applications.